Key Contemporary Concepts : From Abjection to Zeno's Paradox. - Lechte, J. (Theory, culture & society., 2002)
. This book is the essential road-map to the key concepts which frame our understanding of society and culture. From cybernetics to quantum theory, from ideology to power, from aesthetics to mimesis, this book spans a range of disciplines to provide an insight into the current scientific and intellectual state of society. Written by the author of the international bestseller Fifty Key Contemporary Thinkers (Routledge, 1994) this ambitious pedagogical and intellectual project dazzles with insight and the breadth of knowledge presented. Each entry provides a history and current meaning of the co.